Pengaruh Sistem Pembayaran Digital, Cita Rasa dan Harga Terhadap Keputusan Pembelian di Rajaswa Coffee - Aisyah Amini; Dwi Harini; Indah Dewi Mulyani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Research carried out at Rajaswa Coffee, Sitangan Village, Bulakamba District, Brebes Regency. This research aims to determine the influence of digital payment systems, taste and price on purchasing decisions at Rajaswa Coffee. This research is a type of quantitative research. The data collection method used in this research was by interviewing the owner of Rajaswa Coffee and distributing questionnaires. The sample for this research was 90 people who had made purchases at Rajaswa Coffee, using sampling, namely non-probability sampling with a purposive sampling technique. Data analysis in this research is multiple linear regression analysis assisted by SPSS tools. The data obtained is primary data, secondary data is obtained from other media sources such as books and journals related to the focus of this research. The research results show that the digital payment system has a significant influence on purchasing decisions at Rajaswa Coffee, taste has a significant influence on purchasing decisions at Rajaswa Coffee and price has a significant influence on purchasing decisions at Rajaswa Coffee. Then, the results of the simultaneous test show that the influence variables of the digital payment system, taste and price influence purchasing decisions at Rajaswa Coffee.